Investigation of loose contact oxidation kinetic analysis on diesel particulate filters wall surface using non-isothermal TGA technique - Swe Zin Win; Preechar Karin; Watanyoo Phairote; Nuwong Chollacoop; Peerawat Saisirirat; Katsunori Hanamura (My University, 2021)
Abstract Carbonaceous soot particles emitted from diesel engines are dangerous to human health because of its carcinogenic activity and can penetrate into lungs. In order to control soot emissions, diesel particulate filters (DPFs) are widely used to meet progessively stringent regulations of vehicle emissions limits. In this article, the characterization of conventional DPF microstructure was briefly investigated by scanning electron microscopy (SEM) addition with energy dispersive X-ray analysis (EDX) and X-ray fluorescence analysis (XRF). Non-isothermal oxidation mechanism of soot on conventional DPF was carried out from thermogravimetric analysis (TGA) under air atmosphere with the flow rate of 40ml/min at the heating rates of 5, 10, and 15°C/min. The kinetic parameters were calculated by three non-isothermal model-free methods. The average value of apparent activation energy obtained by Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS) and Kissinger (K) were 77.02, 65.29 and 70.48 kJ/mol, respectively at different heating rates. The average results got from this work indicate that non-isothermal experiments were quite low compared to kinetics parameters estimated by the isothermal method from previous research.
Keywords: Isothermal process; Thermogravimetric analysis; Thermal and Kinetic Analysis